Frequency of Iron Deficiency in Females having Normal Haemoglobin level Complaining of Fatigue - Hafiza Sidra tul Muntaha; Afshan Noureen Arain; Muhammad Qasim Ali (Indus Journal of Bioscience Research, 2025)
Background: Iron deficiency is the most widespread nutritional disorder globally and often occurs without anemia, especially in women of reproductive age. Conventional screening practices that rely solely on hemoglobin levels may miss a significant number of cases. Aim: To determine the frequency of iron deficiency in non-pregnant females having normal hemoglobin levels, and to identify associated risk factors based on clinical, demographic, dietary, and reproductive variables. Methodology: A cross-sectional study was conducted at the Department of Medicine, Services Hospital Lahore, over a period of six months. A total of 100 non-pregnant females aged 16–45 years with hemoglobin >11 g/dL were enrolled using non-probability consecutive sampling. Data on sociodemographic, clinical, dietary, and reproductive factors were collected. Laboratory evaluation included hemoglobin, serum ferritin, and serum iron. Iron deficiency was defined as serum ferritin